2019
DOI: 10.1021/acs.biochem.8b01211
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Pore Hydration in Channelrhodopsin by Site-Directed Infrared-Active Azido Probes

Abstract: Channelrhodopsins (ChRs) are retinal binding membrane proteins found in single-cell algae. Photoisomerization of ChRs leads to formation of an ion channel. The resulting change in membrane voltage modulates flagellate motions allowing phototaxis and photophobic responses. Heterologously expressed in host cells, ChRs allow the evocation or suppression of changes in membrane potential with high spatio-temporal resolution -this method has become known as optogenetics. Functional studies have raised questions conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 247 publications
(1,029 reference statements)
2
7
0
Order By: Relevance
“…Our results indicate that CNF residues inserted in selected positions of EL222 can, after a careful scrutiny, provide residue-specific information on the photocycle not attainable by other probes naturally present in EL222, like the FMN chromophore or the protein backbone. This observation is in line with previous studies on other photoreceptors that, in contrast to our work, focused on a relatively low number of unnatural residues (typically less than ten) or did not comprehensively address their potential perturbation (23,24,(28)(29)(30)58). Based on our results with a large collection of mutants (45 for a protein of 210 residues), a major caveat of genetically encoded non-canonical side-chains as site-specific infrared reporters is the risk of mis-or over-interpretations when only a limited number of such probes are tested.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicate that CNF residues inserted in selected positions of EL222 can, after a careful scrutiny, provide residue-specific information on the photocycle not attainable by other probes naturally present in EL222, like the FMN chromophore or the protein backbone. This observation is in line with previous studies on other photoreceptors that, in contrast to our work, focused on a relatively low number of unnatural residues (typically less than ten) or did not comprehensively address their potential perturbation (23,24,(28)(29)(30)58). Based on our results with a large collection of mutants (45 for a protein of 210 residues), a major caveat of genetically encoded non-canonical side-chains as site-specific infrared reporters is the risk of mis-or over-interpretations when only a limited number of such probes are tested.…”
Section: Discussionsupporting
confidence: 92%
“…In this context it is interesting to refer to the recent study by Kurttila et al who introduced para -azidophenylalanine at different positions in the prototypical phytochrome Dr BphP from Deinococcus radiodurans, among them were also the analogous positions studied in this work, i.e., Phe203 (Phe192 in Agp2) and Tyr176 (Tyr165 in Agp2) . The frequencies of the azide stretching modes respond to changes of the molecular environment, however, much less sensitive to variations of the electric field in a quantifiable fashion. Instead, the azide modes are considered as rather qualitative sensors for polarity changes. Nevertheless, for Dr BphP, a significant downshift of the azide stretching mode from Pr → Pfr was reported and interpreted in terms of an increased polarity in Pfr .…”
Section: Discussionmentioning
confidence: 82%
“…By using the spectrally isolated band from (N 3 )­Phe at ∼2100 cm –1 and its sensitivity toward polarity changes, the authors deduced hydration changes at various sites of the putative ion permeation pore. Thanks to these probes they could spatially localized a hydration event in ReaChR that correlates with ion conductivity . In a final example, (N 3 )­Phe was incorporated in place of a Met and a Trp near the FAD of the BLUF photoreceptor PixD and AppA .…”
Section: Tools For Band Assignmentmentioning
confidence: 99%
“…Combined with results obtained with other labeled sites, they concluded that helix F rotates in Meta I, which brings the azido group from a hydrophilic to a hydrophobic environment, a conformational change preceding the formation of the active state of the receptor in Meta II. More recently, Krause et al 761 also introduced site-specifically the unnatural amino acid (N 3 )Phe at different positions of the channelrhodopsin ReaChR. They used the introduced azide probe as a local polarity sensor, aiming to probe the formation and collapse of the ion-conducting pore.…”
Section: Use Of Natural and Unnatural Amino Acids As Local Probesmentioning
confidence: 99%
See 1 more Smart Citation